Green Synthesis and Characterization of Silver Nanoparticles Synthesized Using Leaf Extract of Passiflora Foetida Linn - Lade, Bipin; Patil, Anita (Journal of Sustainable Materials Processing and Management, 2022)
The silver nanoparticles (SNPs) are applied in nanomedicine, health, food safety and other applications. The topical methods are based on chemicals that are toxic in nature, thus to minimize the hazardous effects the naturnal sources needs to be explored for synthesizing SNPs. The contemporary work reports the greener way of silver nanoparticles (SNPs) fabrication using phytochemical, functional groups and secondary metabolites from Passiflora aqueous leaf extract. The optimized condition for SNPs systhesis was 1 mM AgNO3 95ml + leaf extract 5 ml at alkaline pH 11 yields stable NPs. Various parameters such as temperature, pH, sunlight, dark, different concentration of AgNO3 were evaluated. The uv-spectroscopic analysis confirms SNPs synthesis at 420 nm for sun light based, 428 nm at room temperature and 425 nm for microwave based conditions. The FTIR determines alkanes, alkyne, amines, aliphatic amine, carboxylic acid; nitro-compound from the leaf extract have been used for reducing silver nitrate for SNPs synthesis. The SEM and TEM analysis confirms the 14.96 nm size SNPs under sun light condition shows antimicrobial activity against E. coli and S. aureous pathogens at 50 ug/ml concentration, which may have applicability to raised SNPs based green sustinable products in treating pathogens